2021
DOI: 10.1021/acsfoodscitech.1c00347
|View full text |Cite
|
Sign up to set email alerts
|

Food Additives Benzoic Acid and its Methyl and Propyl Parahydroxy Derivatives Aggregate Proteins

Abstract: Benzoic acid and its methyl and propyl para-hydroxy derivatives are approved food preservatives and flavoring agents. Inclusive use of these additives in food, pharmaceuticals, and beauty and healthcare industries however raises concern about the quality and shelf life of the products. The safety levels of benzoates are controversial, even though studies have indicated that they may produce adverse health effects. This study employs nuclear magnetic resonance (NMR), infrared (IR), fluorescence anisotropy, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, there is evidence indicating that proteins can bind benzoate and then the benzoate-bound proteins enter the aggregation pathway to produce amorphous and fibrillar structures. It is important that the concentration of benzoates needed to induce protein aggregation is much lower than the microbicidal and inhibitory concentrations prescribed by the FAO [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence indicating that proteins can bind benzoate and then the benzoate-bound proteins enter the aggregation pathway to produce amorphous and fibrillar structures. It is important that the concentration of benzoates needed to induce protein aggregation is much lower than the microbicidal and inhibitory concentrations prescribed by the FAO [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…While studying aspects of food preservative binding to globular proteins, we found in 2021 that the benzoate class of food additives perturbs the native states of lysozyme, cytochrome c, and myoglobin and transforms the protein population to a mixture of amorphous and amyloid fibrillar aggregates, presumably via denatured or quasi-native states . A study soon after showed that benzoates induce amyloid fibrillation of an intrinsically disordered protein (IDP) as well, raising concerns about the safety and use of synthetic food additives.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we have reported the thermodynamic based study of aqueous solvation and dissociation of benzoic acid at Kelvin temperature range in between of 288 K to 318 K. In series of aromatic acids the benzoic acid (C 6 H 5 COOH) is a colorless crystalline solid (M.P. 395 K) substance having a very poor solubility into cold water with pleasant smell and used in food additives [10,11]. In derivatives of benzoic acid the ortho-hydroxybenzoic acid (salicylic acid) have solubility in respective solvents with greater importancy for medicinal purposes as antibacterial, anti-inflammatory and in skin diseases well [12].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%